Binding Cofactors with Triplex‐Based DNA Motifs. Issue 47 (5th November 2013) - Kröner, Christoph; Göckel, Anja; Liu, Wenjing; Richert, Clemens
Abstract Cofactors are pivotal compounds for the cell and many biotechnological processes. It is therefore interesting to ask how well cofactors can be bound by oligonucleotides designed not to convert but to store and release these biomolecules. Here we show that triplex‐based DNA binding motifs can be used to bind nucleotides and cofactors, including NADH, FAD, SAM, acetyl CoA, and tetrahydrofolate (THF). Dissociation constants between 0.1 μM for SAM and 35 μM for THF were measured. A two‐nucleotide gap still binds NADH. The selectivity for one ligand over the others can be changed by changing the sequence of the binding pocket. For example, a mismatch placed in one of the two triplets adjacent to the base‐pairing site changes the selectivity, favoring the binding of FAD over that of ATP. Further, changing one of the two thymines of an A‐binding motif to cytosine gives significant affinity for G, whereas changing the other does not. Immobilization of DNA motifs gives beads that store NADH. Exploratory experiments show that the beads release the cofactor upon warming to body temperature.